1995
DOI: 10.2165/00003495-199549060-00004
|View full text |Cite
|
Sign up to set email alerts
|

Drug Treatment Associated with Heart Valve Replacement

Abstract: This article reviews a number of specific pharmacological considerations for patients with prosthetic heart valves. All patients with mechanical heart valves should be anticoagulated. In the past, an International Normalised Ratio (INR) of 2.5 to 4.5 has been recommended. Recent nonrandomised studies have suggested that a patient with a prosthetic valve who is at low risk for thromboembolic events could have an INR ranging from 1.8 to 3.5. The lower end of this range should only be used for patients at higher … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

1998
1998
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 56 publications
0
4
0
Order By: Relevance
“…This is especially the case in patients with prosthetic cardiac valves. 15 One other recent review suggested that withholding warfarin for 48 h was associated with a 1 point fall in the INR from about 3.5 to 2.5 in patients with prosthetic valves. This value was not associated with increased bleeding or increased thrombotic episodes over the transient period of drug withdrawal.…”
Section: Vitamin K Antagonistsmentioning
confidence: 99%
“…This is especially the case in patients with prosthetic cardiac valves. 15 One other recent review suggested that withholding warfarin for 48 h was associated with a 1 point fall in the INR from about 3.5 to 2.5 in patients with prosthetic valves. This value was not associated with increased bleeding or increased thrombotic episodes over the transient period of drug withdrawal.…”
Section: Vitamin K Antagonistsmentioning
confidence: 99%
“…Patients with mechanical heart valve replacement need to have life-time anticoagulation with warfarin [ 9 ]. Since warfarin metabolism is affected by the patient’s age, gender, genotype, drugs and other factors, the therapeutic window of warfarin is narrow and serious complications such as bleeding or thrombosis may occur.…”
Section: Discussionmentioning
confidence: 99%
“…Reported thromboembolism rates of bioprosthetic valves range from 0.5% to 3% per year without the use of anticoagulants [26,27]. This thromboembolism rate is comparable to anticoagulated patient with mechanical valves.…”
Section: The Patient On Warfarin Who Desires To Become Pregnantmentioning
confidence: 93%
“…This risk is not well established and may be less than 1% per day. For example, the average yearly risk of thromboembolic events with a mechanical valve without anticoagulation is 10% per year or 0.2% per day [26,30]. However, valve thrombosis or an embolic event can be catastrophic.…”
Section: Surgerymentioning
confidence: 99%